2018
DOI: 10.1002/uog.18905
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester risk assessment based on ultrasound and cell‐free DNA vs combined screening: a randomized controlled trial

Abstract: Our study has shown that first-trimester risk assessment for trisomy 21 that includes a detailed ultrasound examination as well as NT measurement and is followed by cfDNA testing is associated with a significant reduction in the false-positive rate compared with FTCS. This approach obviates the need for maternal serum free β-human chorionic gonadotropin and pregnancy-associated plasma protein-A in screening for fetal aneuploidy. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 39 publications
1
53
0
4
Order By: Relevance
“…Only cases with an NT ≤3.5 mm and cases without major defects were included in randomization to these two screening protocols. The results of the original study have been reported elsewhere [9].…”
Section: Methodsmentioning
confidence: 68%
See 2 more Smart Citations
“…Only cases with an NT ≤3.5 mm and cases without major defects were included in randomization to these two screening protocols. The results of the original study have been reported elsewhere [9].…”
Section: Methodsmentioning
confidence: 68%
“…The detailed power calculation of the original study is described elsewhere [9]. In summary, we assigned 700 women to each study arm in order to demonstrate a significant difference in the false-positive rate of both approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the five included studies, one used a randomized controlled trial design, three were cohort studies, and one used an uncontrolled before‐after design . Two studies were single centre studies from Germany and Spain, respectively, one study included three centres in Canada, and two studies were performed in‐house by the manufacturer of the cfDNA test and retrospectively analyzed frozen samples from an unclear number of centres …”
Section: Resultsmentioning
confidence: 99%
“…In total, 3074 samples were successfully tested using a microarray‐based cfDNA test and had a suitable reference standard, including 187 T21, 43 T18, and 19 T13 cases. Four studies included women with singleton pregnancies only, and one study included a mixed population of singleton and twin pregnancies (759 and 40 women, respectively) …”
Section: Resultsmentioning
confidence: 99%